Light pollution: Assessment of sky glow on two dark sky regions of Portugal. Issue 7 (2nd April 2016) - Lima, Raul Cerveira; Pinto da Cunha, José; Peixinho, Nuno
ABSTRACT: Artificial light at night (ALAN), producing light pollution (LP), is not a matter restricted to astronomy anymore. Light is part of modern societies and, as a consequence, the natural cycle day–night (bright–dark) has been interrupted in a large segment of the global population. There is increasing evidence that exposure to certain types of light at night and beyond threshold levels may produce hazardous effects to humans and the environment. The concept of "dark skies reserves" is a step forward in order to preserve the night sky and a means of enhancing public awareness of the problem of spread of light pollution worldwide. The aim of this study was to assess the skyglow at two sites in Portugal, the Peneda-Gerês National Park (PNPG) and the region now known as Dark Sky Alqueva Reserve. The latter site was classified as a "Starlight Tourism Destination" by the Starlight Foundation (the first in the world to achieve this classification) following a series of night sky measurements in situ described herein. The measurements at PNPG also contributed to the new set of regulations concerning light pollution at this national park. This study presents the first in situ systematic measurements of night sky brightness, showing that at the two sites the skies are mostly in levels 3 to 4 of the Bortle 9-level scale (with level 1 being the best achievable). The results indicate that the sources of light pollution and skyglow can be attributed predominantly to contamination from nearby urban regions.